A1.4 Building a better hospital experience with lego ©: a pilot study. (4th October 2017) - Miah, J; Prestidge, M; Hovey, S; Bathgate, F; Cochrane, D; Cooper, J
Abstract : Background: General anaesthetic, or sedation, is routinely used for children who are unable to cope with the distress of an MRI scan. Due to risks and costs, alternatives to reduce anxiety are used where possible, including play based therapy. Evidence has shown that using a mock MRI scanner can help alleviate anxiety. Our aim was to use a Lego © model scanner (model commissioned and built by Bright Bricks) in conjunction with the explanation provided to the children about what will happen during the scan. Methods: Eligible children were asked if they had had a scan before and whether they felt worried about having the scan, they were asked to rate this on a distress thermometer scale of 1–10 (1=not worried, 10=extremely worried). Children were given the model scanner to play with and the process of having a scan was demonstrated and discussed by the health care professional. After playing with the Lego © model children were asked to fill in the distress thermometer again answering how they feel about having the MRI scan after playing with the model. Results: Data from 31 children were collected between April 2015 and October 2016, with a mean age of 9.3. 79% of participants felt that the Lego © model improved their worry making them less worried about the scan. Statistical analysis showed a significant reduction in worry after playing with the model (p=0.001). In memory of Dr Jenny Miah